The Effect of Adding Sugar Cane (Saccharum officinarum L.) Water in Skim Milk and Egg Yolks on The Quality of Simmental Cow - Ester Liana Br Ginting; Efrida Pima Sari Tambunan; Syukriah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Sugarcane is a type of grass plant that is widely cultivated by the community and has a fairly high nutritional content. Sugarcane juice contains sucrose which consists of glucose and fructose. Sucrose contained in sugarcane juice serves as a source of energy for spermatozoa. This study aims to determine the effect of adding sugarcane juice to skim milk diluent and egg yolk on motility, viability and semen abnormalities of Simmental cattle. This research was conducted at the UPT Artificial Insemination Department of Food Security and Animal Husbandry of North Sumatra Province. The method used in this study was a completely randomized design with 5 treatments and 4 replications consisting of P0: Skimmed milk and egg yolk diluent without sugarcane juice, P1: Skim milk and egg yolk diluent + 25 ml of sugarcane juice, P2: Milk diluent skim and egg yolk + 35 ml of sugarcane juice, P3: Diluent of skim milk and egg yolk + 45 ml of sugarcane juice. Parameters measured were motility, viability and sperm abnormalities of Simmental cattle semen. The results of this study indicate that the P1 treatment with 25 ml of sugarcane juice was able to maintain motility during 72 hours of storage by 40%, the highest mean value of spermatozoa viability during 144 hours of storage (60.90% ± 1.08), and the lowest spermatozoa abnormality value during storage 144 hours (17.10% ± 1.08). The conclusion of this study was that 25 ml of sugarcane juice in skimmed milk and egg yolk diluent could maintain the quality of Simmental cattle spermatozoa.